The role of multiple ionization of H2O in heavy ion collisions - Bachi, Nicolás (2019)
Collisional ionization processes involving H2O molecules and C6+, O8+, Si13+ ions are studied by means of the classical trajectory Monte Carlo method using molecular orbital calculations to define the ionization stages of the water molecule. Net total and single-differential cross sectionsin energy and angle are obtained by using a newly developed model that goes beyond the commonly applied oneactive electron approximation. This model allows us to access the fraction of electron emission arising from single and multiple electron ionization. Calculated cross sections are contrasted and benchmarked against available experimental data at impact energies in the MeV/u range. The present results highlight the important role of multiple ionization in the emission of electrons where we find the majority of electrons emitted with energies greater than ~50eV arise from multiple ionization collisions.